Empowering educational leaders for AI integration in rural STEM education: Challenges and strategies - Kim, Juhee; Wargo, Elizabeth (Frontiers in Education, 2025)
This study explored the role of educational leaders in integrating artificial intelligence (AI) into rural K-12 STEM education. The research focused on the perceptions, strategies, and barriers that educational leaders face in navigating AI integration, particularly in the unique context of rural schools. Drawing on survey and focus group data from rural school leaders, this study examined how rural educational administrators perceive AI’s potential and the challenges associated with its adoption. It provided insights into leadership strategies for addressing infrastructural limitations, fostering professional development, and ensuring equitable AI adoption. Ultimately, this research aimed to empower rural educational leaders to harness AI technologies to enhance STEM education.